1984
DOI: 10.1254/jjp.36.23
|View full text |Cite
|
Sign up to set email alerts
|

Effect of α1- and α2-Adrenoceptor Agorists and Antagonists on ACTH Secretion in Intact and in Hypothalamic Deafferentated Rats

Abstract: Abstract-The effect of systemically injected a, and a2-adrenoceptor agonists and antagonists on ACTH secretion was studied in rats. Epinephrine, norepin ephrine, phenylephrine, clonidine, B-HT933, and B-HT920 caused a significant and dose-related increase of the ACTH concentration in the serum. The order of median effective dose (ED50) of these drugs on ACTH secretion was as follows: epinephrine norepinephrine < B-HT920 < clonidine < phenylephrine <; B-HT933. Isoproterenol, a ,3-adrenoceptor agonist, had no ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 40 publications
(10 reference statements)
1
9
0
Order By: Relevance
“…The increase in corticosterone concentration induced by phentolamine is in agreement with the observation of Shimizu (1984), who found that the drug in question used in doses of 5 mg/kg or higher stimulates the ACTH secretion. …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The increase in corticosterone concentration induced by phentolamine is in agreement with the observation of Shimizu (1984), who found that the drug in question used in doses of 5 mg/kg or higher stimulates the ACTH secretion. …”
Section: Resultssupporting
confidence: 91%
“…Dexamethasone decreased the plasma corticosterone concentration (though ACTH (Shimizu, 1984) concentrations on its own-it was high enough to effectively block the elevation of corticosterone level induced by the %-adrenoceptor agonist clonidine (Przegalifiski etal., 1989). The increase in corticosterone concentration induced by phentolamine is in agreement with the observation of Shimizu (1984), who found that the drug in question used in doses of 5 mg/kg or higher stimulates the ACTH secretion.…”
Section: Resultsmentioning
confidence: 99%
“…Shimizu 35 stated that agonists (NE and PE) of 36 Handley and Mithani, 37 Yorimitsu et al 38 Jager et al 39 stated that doxazosin had a negative effect on aldosterone secretion by adrenocortical cells porcine. Mulatero et al 40 found that an intravenous administration of doxazosin to patients with primary aldosteronism significantly lowered plasma aldosterone concentration.…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, the stress-reduction hypothesis may be tentatively related to the binding data summarized above, showing that the most significant increase of the cx2-adrenoceptors was observed in the hypothalamus. Moreover, there is clear evidence that noradrenaline inhibits corticotrophin (ACTH) secretion by an action on the hypothalamus (see reviews in Amaral & Sinnamon, 1977;Ganong, 1980;Jones et al, 1984), and it seems that the inhibition of the corticotrophin-releasing factor by noradrenaline is mediated by an cx-adrenoceptor mechanism (Buckingham & Hodges, 1979;Ganong, 1980;Shimizu, 1984). Thus, it is conceivable that the increase in number of hypothalamic cx2-receptors observed after stimulation of the LC modulates the noradrenergic control of the ACTH release.…”
Section: Discussionmentioning
confidence: 99%